The Corrosion Resistance of Graphene-Modified Oily Epoxy Coating on AZ31 Magnesium Alloys - Gao, Zhengyuan; Sun, Chengjin; Du, Lianteng; Yang, Dong; Zhang, Xiang; An, Zhiguo (Frontiers in Materials, 2021)
In order to enhance the corrosion resistance of AZ31 magnesium alloy, graphene-modified oily epoxy resin coating (G/OEP) were prepared on the surface of magnesium alloy. SEM observations show that graphene has fewer surface defects, and can significantly improve the surface quality of the coating and reduce defects. FI-TR testing shows that coating are mainly composed of epoxy resin (polyurethane) and its corresponding curing agent. Electrochemical testing shows that the coating can provide good corrosion protection for magnesium alloy. Compared with the corrosion current density of magnesium alloy of 6.20 × 10−7 A/cm2, the G/OEP can significantly reduce the corrosion current density to 6.96 × 10−12 A/cm2. Analysis of the morphology of the coating after electrochemical corrosion found that graphene can improve the shielding ability of the coating to corrosive media, and reduce the damage of corrosion to the coating structure, and enhance the corrosion resistance of the coating. The content of graphene for excellent corrosion resistance of coating during this experiment is 0.6 wt%. The graphene can fill the defects generally in the coating during the curing process to prevent substrate from penetration of corrosive media caused by the density and hydrophobicity of coating are increased.